Development of the health care market – forecasts for the future - Furtak, Marzena; Książek, Piotr; Warchoł-Sławińska, Ewa; Drop, Bartłomiej; Włoch, Krzysztof; Kulbaka, Ewa (Polish Journal of Public Health, 2011)
At the time of the growing demand for health services, resulting inter alia from progressing ageing of society, one should seek novel approaches, solutions and tools to assist difficult processes of transformations of the health care sector with the forthcoming new challenges. Application of solutions of teleinformatic technologies called “e-Health” which effectively help to satisfy the needs of patients, medical specialists, medical service providers and decision-makers of this sector, is gaining here a particular relevance. The examples of tools and solutions of e-Health include networks of medical information, systems of acquisition of patients’ medical data coming from various health care units, telemedical services, medical portals and a lot of other tools based on information-communication technologies assisting prevention, diagnosing, treatment, health monitoring and keeping appropriate lifestyle. In the age of transformations and trends for implementing innovative changes, implementing solutions of teleinformatic technologies that can become the driving force of this sector, is fully justified and accurate.